Legenda vetus, Acta processus canonizationis, et Miracula Sanctae Margaritae de Hungaria = The oldest legend, Acts of the canonization process, and Miracles of Saint Margaret of Hungary - Csepregi, Ildikó; Csepregi, Ildikó; Klaniczay, Gábor; Péterfi, Bence, 1985-; Flanigan, C. Clifford; Perraud, Louis A. (Louis Alan) (Central European medieval texts, 2018)
This bilingual volume (Latin text with English translation) is the second in the series presenting hagiographical narratives from medieval Central Europe. It contains the most important hagiographical corpus of medieval Hungarian history: that of Saint Margaret (1242-1270), daughter of King Béla IV, who lived her life as a Dominican nun. Margaret's cult started immediately after her death and the demand to examine her sanctity was first formulated in 1272. The canonization process recommenced in 1276, followed by further initiatives across the centuries. Margaret was eventually canonized only in 1943. Besides the full Latin text and the English translation of her oldest legend, written between 1272 and 1275, this volume contains the acts of the 110 testimonies of the papal investigation concerning her sainthood, recorded between July and October 1276 and prepared from existing source editions. In addition, the editors include a series of recently discovered documents, including a petition by the bishop of Várad (Oradea) to promote the cause, and the notarial records of a set of miracles that occurred at Margaret's grave in the second half of the fifteenth century. The annotated bilingual text is complemented by a select bibliography on Saint Margaret and her hagiography.